1993
DOI: 10.1073/pnas.90.1.168
|View full text |Cite
|
Sign up to set email alerts
|

The role of zinc fingers in transcriptional activation by transcription factor IIIA.

Abstract: We have described elsewhere a number of the properties of a set of mutant forms of Xenopus transcription factor IIIA (TFIIIA) containing single amino acid substitutions that result in the structural disruption of individual zinc finger domains. These "broken finger" proteins have now been analyzed with respect to their ability to support transcription of 5S rRNA genes in vitro. Disruption of any one of the first six zinc fingers of TFIIIA has no discernible effect on the activity of the protein in supporting 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Our observation of compensatory binding and energetic buffering, combined with our previous report on the insensitivity of TFIIIA function in in vitro transcription assays to the binding affinity of TFIIIA in binary complexes with the 5 S rRNA gene (63), may provide an explanation for this lack of sequence conservation. We suggest that mutational alterations in TFIIIA would have relatively modest effects on DNA binding affinity and that the ultimate effects of these changes on the transcriptional function of TFIIIA would be further mitigated by the tremendous stabilization of binding that is afforded by the subsequent association of TFIIIC and TFIIIB.…”
Section: Table IV Dna Bending Induced By Binding Of A1-100 and A100 -mentioning
confidence: 90%
“…Our observation of compensatory binding and energetic buffering, combined with our previous report on the insensitivity of TFIIIA function in in vitro transcription assays to the binding affinity of TFIIIA in binary complexes with the 5 S rRNA gene (63), may provide an explanation for this lack of sequence conservation. We suggest that mutational alterations in TFIIIA would have relatively modest effects on DNA binding affinity and that the ultimate effects of these changes on the transcriptional function of TFIIIA would be further mitigated by the tremendous stabilization of binding that is afforded by the subsequent association of TFIIIC and TFIIIB.…”
Section: Table IV Dna Bending Induced By Binding Of A1-100 and A100 -mentioning
confidence: 90%
“…The crystal structure of the five-finger Gli protein-DNA complex showed that, in other subclasses, separate zinc fingers can contribute unequally to DNA recognition (26). Furthermore, some Cys 2 /His 2 zinc fingers have been shown to mediate protein contacts (7,21), subcellular localization (19), or a puzzling nuclease activity (12). Therefore, for a given protein, the role of individual Cys 2 /His 2 fingers in both DNA binding and protein-protein contacts remains an open question.…”
mentioning
confidence: 99%
“…Protein-protein interactions with the zinc fingers could account for this stabilization. A role for zinc fingers in transcriptional activation distinct from DNA binding has been suggested (13). Complex stability is not a prerequisite for transcription (51), so differences in stability of complexes formed with C-terminal mutants are not necessarily reflected by changes in transcriptional activation.…”
Section: Resultsmentioning
confidence: 99%
“…Carboxyl-terminal zinc fingers may also be required for transcriptional activation in addition to DNA binding. Disruptions of single zinc fingers in the C-terminal portion of the zinc finger domain, made by mutation of a single histidine to asparagine, result in reduced transcription without changing the affinity of TFIIIA for the ICR (13).…”
Section: Activation Of Transcription By Tfiiia 7497mentioning
confidence: 99%
See 1 more Smart Citation